The Influence of Colleague Knowledge Base, Trust Capability, and Role of Trust on Employee Performance - Deni Surapto; Irmawaty; Arie Wibowo Khurniawan; Nenah Sunarsih (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Education in the era of globalization and digitalization has become increasingly complex, requiring institutions to provide flexible learning and open access. Employee performance in such settings depends on internal factors, including colleagues’ knowledge, trust, and trust capability. This study aims to analyze the effects of colleagues’ knowledge base, the role of trust, and trust capability on employee performance. Using a quantitative approach with SEM-PLS analysis and a sample of 235 employees, the results indicate that all variables, both directly and indirectly through mediation, positively and significantly influence performance. The findings show that the Role of Trust positively affects employee performance, colleagues’ knowledge base influences performance through trust, and trust capability enhances performance by strengthening trust. Practically, fostering work dedication, proper management of organizational information, conflict reduction, and adherence to instructions are essential to optimize employee performance. The study contributes empirical evidence that integrating colleagues’ knowledge and trust mechanisms can significantly enhance performance in university settings, providing actionable guidance for higher education management and organizational development.